Spousal influences on parents' non-market time choices - Rachel Connelly; Jean Kimmel (Institute for the Study of Labor (IZA), 2007)
This paper considers the effect of spouse's characteristics on three aggregated non-paid time uses, active leisure time; child caregiving time; and home production time, using the American Time Use Survey (ATUS). The time diary of each married individual with children under the age of 13 (mothers and fathers) is analyzed, both in terms of the level of non-paid time and the wife's share of the total level of the daily activity for the couple. Three spousal variables: the relative wage of the wife compared to her husband, spouses' weekly hours of employment; and, in the level equations only, the spouses' time in the same activity are considered. Each of these spousal variables needs to be estimated in order to address issues of both endogeneity and missing data. Three alternative strategies to address these problems are explored: predictions within the sample, predictions from outside the sample and propensity matching which marries mothers with time diaries to fathers with time diaries who have propensity scores similar to the women's husband. The results show very little effect of one spouse on the level of other spouse's unpaid time use. This absence of spousal effects is similar to the reduction of spousal effects in employment time described in Blau and Kahn (2005). In terms of the share of wife's time in the activity, we find higher relative wages of the mother compared to her husband leads to a greater share of child care done by the mother on both weekdays and weekends. No consistent effect of relative wages is found on the mother's share of leisure or home production.
Keywords: 330; Familienökonomik; Zeitallokation; Hausarbeit; USA